Discovery of a Novel Scaffold as an Indoleamine 2, 3‐Dioxygenase 1 (IDO1) Inhibitor Based on the Pyrrolopiperazinone Alkaloid, Longamide B. (5th December 2016) - Shiokawa, Zenyu; Kashiwabara, Emi; Yoshidome, Daisuke; Fukase, Koichi; Inuki, Shinsuke; Fujimoto, Yukari
Abstract: Indoleamine 2, 3‐dioxygenase 1 (IDO1) has emerged as a key target for cancer therapy, as IDO1 plays a critical role in the capacity of tumor cells to evade the immune system. The pyrrolopiperazinone alkaloid longamide B and its derivatives were identified as novel IDO1 inhibitors based on docking studies and small library synthesis. The thioamide derivative showed higher IDO1 inhibitory activity than longamide B, and displayed an activity similar to that of a representative IDO1 inhibitor, 1‐methyl‐tryptophan. These results suggest that the pyrrolopiperazinone scaffold of longamide B could be used in the development of IDO1 inhibitors. Abstract : A new scaffold : The pyrrolopiperazinone alkaloid longamide B and its derivatives were identified as novel IDO1 inhibitors based on docking studies and small library synthesis. The thioamide derivative showed higher IDO1 inhibitory activity than longamide B and displayed activity similar to that of a representative IDO1 inhibitor, 1‐methyl‐tryptophan. These results suggest that the pyrrolopiperazinone scaffold of longamide B could be used for IDO1 inhibitors.